The Impact of Word of Mouth and Customer Satisfaction on Purchase Decisions: The Role of Maslahah as an Intervening Variable in the Cosmetic Products Industry in Indonesia - K, Amiruddin; Astuti, An Ras Try; ., Mujahidin (Journal of Ecohumanism, 2024)
This study investigates how Word of Mouth (recommendations), Customer Satisfaction, and perceived Maslahah influence Purchase Decisions in the cosmetic product consumption context in Indonesia. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed to analyze data from 450 respondents. Results indicate that Word of Mouth significantly influences Purchase Decisions (β = 0.350, t-stat = 5.698, p < 0.000), suggesting positive recommendations increase the likelihood of product purchase. However, Word of Mouth slightly diminishes the perception of product Maslahah (β = -0.122, t-stat = 1.835, p = 0.067), implying positive recommendations may marginally affect perceived maslahah. The indirect effect of Word of Mouth on Purchase Decisions through Maslahah was also marginal (β = -0.044, t-stat = 1.829, p = 0.068). Customer Satisfaction significantly enhances the perception of product Maslahah (β = 0.720, t-stat = 11.309, p < 0.000) and influences Purchase Decisions through Maslahah (β = 0.263, t-stat = 7.194, p < 0.000), yet direct impact on Purchase Decisions was insignificant (β = -0.002, t-stat = 0.044, p = 0.965). Moreover, perceived Maslahah significantly affects Purchase Decisions (β = 0.366, t-stat = 7.586, p < 0.000), highlighting its role in consumer decision-making. Overall, findings deepen understanding of how Word of Mouth, Customer Satisfaction, and perceived Maslahah shape consumer behavior in purchasing cosmetics. Marketers can utilize these insights to leverage recommendations, enhance satisfaction, and communicate product benefits effectively to influence consumer decisions, thereby enhancing market position and competitive advantage for cosmetic companies.